Primary ecological succession of marine communities on the Tajogaite lava flows (La Palma, Canary Islands), fishes colonize faster than macroinvertebrates and algae - Sangil, Carlos; Álvarez-Canali, Daniel; Reyes, Javier; Rodríguez, Julián; Sansón, Marta (Frontiers in Marine Science, 2024)
We studied the primary succession of benthic communities in the lava flows of the Tajogaite volcano at 2, 4.5, and 7 months after the eruption ended. The lava from the Tajogaite created several lava flows and sterile rocky reefs that were monitored in both intertidal and subtidal areas up to 20 m depth. Sampling included macroinvertebrates and algae in the intertidal, and fishes, macroinvertebrates, and algae in the subtidal. A control zone was selected to compare the early colonisation of lava flows with that of a mature ecosystem. Colonisation of the lava flow was swift, with numerous species arriving and proliferating soon after the eruption ended. After 7 months, the total number of species recorded in the lava flows was 70, representing 64% of those found in the control zone. thus, communities were gradually becoming increasingly complex owing to the continuous incorporation of species. The number of fishes, and macroinvertebrates in both the intertidal and subtidal, lava flows increased progressively, approaching the values of the control zone. However, algae, in terms of total cover, presented values similar to the control zone from the beginning of the monitoring. All the communities have followed the same trajectory to converge towards communities like those in the control zone, although the rate at which they have changed with time differs. After seven months, differences in fishes between lava flows and the control zone were small, but they were still large with respect to macroinvertebrates and algae. Thus, according to each community of organisms, the benthic ecosystem of the lava flows was found at different stages of succession.